Neuropsychological characteristics as predictors of SSRI treatment response in depressed subjects - Gorlyn, Marianne (2008)
Studies suggest that neuropsychological measures may provide prognostic information regarding SSRI treatment response, yet it is unclear which specific cognitive domains are the most effectual predictors. The aim of this study was to characterize the cognitive profile associated with SSRI nonresponse using a comprehensive set of neuropsychological tests. Participants (N = 32) met criteria for current major depressive episode. Assessment followed pre-treatment medication washout. Clinical response was measured after 3-month open-label SSRI treatment. Groups did not differ by demographic characteristics, intelligence or depression severity. Responders outperformed nonresponders across all cognitive domains, with the largest differences observed in executive, language and working memory functions. Results indicate poorer global cognitive functioning is predictive of treatment nonresponse. Deficits were most pronounced in tests demanding greater mental search and manipulation rather than speeded motor output. Cognitive slowing may mediate the working memory and executive function deficits found in nonresponders. These findings can inform exploration for pharmacogenetic endophenotypes.